2017
DOI: 10.3349/ymj.2017.58.3.564
|View full text |Cite
|
Sign up to set email alerts
|

Signal Detection of Imipenem Compared to Other Drugs from Korea Adverse Event Reporting System Database

Abstract: PurposeTo detect signals of adverse drug events after imipenem treatment using the Korea Institute of Drug Safety & Risk Management-Korea adverse event reporting system database (KIDS-KD).Materials and MethodsWe performed data mining using KIDS-KD, which was constructed using spontaneously reported adverse event (AE) reports between December 1988 and June 2014. We detected signals calculated the proportional reporting ratio, reporting odds ratio, and information component of imipenem. We defined a signal as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…A national pharmacovigilance database enables detection of unknown ADRs in addition to known ADRs. The KIDS-KD has been successfully used to detect signals of several drugs including imipenem and quinolone antibiotics [ 24 , 25 ]. In this study, we were able to detect signals of cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…A national pharmacovigilance database enables detection of unknown ADRs in addition to known ADRs. The KIDS-KD has been successfully used to detect signals of several drugs including imipenem and quinolone antibiotics [ 24 , 25 ]. In this study, we were able to detect signals of cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…8 Research with this method is usually performed to detect unexpected ADRs that are not found in the list of well-documented ADRs found on the drug label information. 27–29 Therefore, continuous monitoring is needed along with cooperation with other epidemiologic studies on drug safety.…”
Section: Discussionmentioning
confidence: 99%
“…A signal was considered to be detected by meeting these indices: the number of cases ≄3, the PRR and ROR≄2, Chi-Squared values ≄4. [ 27 ] The IC is a logarithmic value that can be calculated by dividing the probability of drug use and a specific AE occurrence [P (AE, Drug)] by the product of the individual probabilities of drug use and a specific AE occurrence [P(AE)P (Drug)], if the drug use and the specific AE occurrence are independent. This can be expressed as the following formula: IC = log 2 P (AE, Drug)/P (AE)P (Drug).…”
Section: Methodsmentioning
confidence: 99%